ECAI 2010 - Coelho, Helder (IOS Press, 2013)
Artificial intelligence (AI) is of central importance to contemporary computer science and informatics. Techniques, results and concepts developed under the banner of AI research have not only benefited applications as diverse as medicine and industrial systems applications, but are of fundamental importance in areas such as economics, philosophy, linguistics, psychology and logical analysis. This book contains the proceedings of the nineteenth biennial European Conference on Artificial Intelligence (ECAI), which since 1974 has been Europe’s principal opportunity for researchers to present and hear about the very best contemporary AI research in all its diverse forms and applications. From a total of 607 submitted papers, the 135 full papers selected for presentation after review are collected here, together with a further 91 submissions selected for presentation as short papers. This book is an essential resource for anyone who wishes to keep abreast of the latest developments in the field of AI. The book also includes papers from one of ECAI’s associated conferences: Prestigious Applications of Intelligent Systems (PAIS).